Perancangan Data Warehouse Penjualan Restoran Hotel Grand Allison Sentani dengan Skema Galaxy - Raden Ikka Lestari Puteri; Ramos Somya (Peneliti.net, 2023)
Hotel Grand Allison Sentani Papua is one of the largest hotels in Sentani Papua which has an income of billions of rupiah in one year, where one of its income comes from the sale of hotel restaurants. This hotel uses POS (Point Of Sales) to record daily hotel restaurant sales. Transaction data from the POS has not been stored and processed properly, so that the hotel has not been able to process it into the information needed. In this research, a Data Warehouse is designed using the Galaxy scheme which is implemented with MySQL database engine that is free for use. In addition, a web-based Online Analytical Processing (OLAP) application was developed that utilizes the Highcharts library to display graphs. OLAP applications are developed using the Prototying method. The test results show that the Data Warehouse consisting of two fact tables is useful for accommodating all transaction data so far and the OLAP application created is also able to present information well through graphs processed using the Highcharts library.